2021
DOI: 10.3390/ijms222312848
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Physiological, Transcriptomic, and Metabolomic Analyses Revealed Molecular Mechanism for Salt Resistance in Soybean Roots

Abstract: Salinity stress is a threat to yield in many crops, including soybean (Glycine max L.). In this study, three soybean cultivars (JD19, LH3, and LD2) with different salt resistance were used to analyze salt tolerance mechanisms using physiology, transcriptomic, metabolomic, and bioinformatic methods. Physiological studies showed that salt-tolerant cultivars JD19 and LH3 had less root growth inhibition, higher antioxidant enzyme activities, lower ROS accumulation, and lower Na+ and Cl- contents than salt-suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…In the present study, based on the morphological and physiological responses of S. lycopersicum to salt stress, metabolomic and transcriptomic approaches were used to analyze the DEGs and DAMs of S. lycopersicum roots during various stages of salt stress and to identify significantly enriched KEGG pathways, mainly "biosynthesis of secondary metabolites", "plant hormone signal transduction", and "phenylpropanoid biosynthesis". This is consistent with the results of former works that used a multiomics approach to analyze the response mechanisms and metabolic processes of S. alopecuroides, B. vulgaris, and B. napus roots to salt stress (Liu et al, 2020;Zhu et al, 2021;Wang et al, 2022b), but also differs somewhat from the results of studies on the molecular mechanisms of salt tolerance in G. max roots (Jin et al, 2021).…”
Section: Phenotypic and Physiological Responses Of S Lycopersicum Dur...supporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, based on the morphological and physiological responses of S. lycopersicum to salt stress, metabolomic and transcriptomic approaches were used to analyze the DEGs and DAMs of S. lycopersicum roots during various stages of salt stress and to identify significantly enriched KEGG pathways, mainly "biosynthesis of secondary metabolites", "plant hormone signal transduction", and "phenylpropanoid biosynthesis". This is consistent with the results of former works that used a multiomics approach to analyze the response mechanisms and metabolic processes of S. alopecuroides, B. vulgaris, and B. napus roots to salt stress (Liu et al, 2020;Zhu et al, 2021;Wang et al, 2022b), but also differs somewhat from the results of studies on the molecular mechanisms of salt tolerance in G. max roots (Jin et al, 2021).…”
Section: Phenotypic and Physiological Responses Of S Lycopersicum Dur...supporting
confidence: 92%
“…Since the effective response capacity of plants under salt stress depends on the roots ( Deolu-Ajayi et al., 2019 ; Nakamura et al., 2020 ). A combined metabolome and transcriptome analysis have been carried out in G. max ( Jin et al., 2021 ), S. alopecuroides ( Zhu et al., 2021 ), B. vulgaris ( Liu et al., 2020 ), and B. napus ( Wang et al., 2022b ) roots to reveal the molecular mechanisms underlying their salt tolerance. In the present study, based on the morphological and physiological responses of S. lycopersicum to salt stress, metabolomic and transcriptomic approaches were used to analyze the DEGs and DAMs of S. lycopersicum roots during various stages of salt stress and to identify significantly enriched KEGG pathways, mainly “biosynthesis of secondary metabolites”, “plant hormone signal transduction”, and “phenylpropanoid biosynthesis”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers suggest that maintaining the TCA cycle helps plants survive stress conditions such as high temperature (Li et al, 2016), drought (Li et al, 2017b) and salt stress (Che-Othman et al, 2020). Salt-tolerant soybean varieties have higher amino acid accumulation rate and faster TCA cycle activity (Jin et al, 2021). Some scholars also pointed out that wild soybean (Li et al, 2017a) promoted its energy metabolism and intermediate metabolite levels under saltalkali stress by increasing TCA cycle activity, thus enhancing salt tolerance.…”
Section: Potassium Improved the Salt Tolerance Of Cotton By Promoting...mentioning
confidence: 99%
“…Previous studies have used integrated transcriptomic and metabolomic analysis to examine abiotic stress in plants. It was found that isoflavones were differentially expressed under drought stress in soybean and isoflavones played an important role in the regulation of ROS [ 22 ]. In tobacco, it was reported that increased polyphenol content may protect against low temperature stress [ 23 ].…”
Section: Introductionmentioning
confidence: 99%